Narrative Innovation In The Age Of Streaming: Algorithmic Storytelling And The Anthological Aesthetics Of Love, Death & Robots - Houssem Eddine MERZOUGUI (Akofena)
Abstract: This study explores the evolution of digital storytelling through a case analysis of Love, Death & Robots, a Netflix Original anthology series that exemplifies narrative innovation on streaming platforms. Anchored in media theory and digital narrative scholarship, the research investigates how the series’ database-driven structure, algorithmically informed production logic, and thematic diversity reflect and reshape storytelling conventions in the digital media environment. Drawing on a multi-methodological approach that includes close textual analysis and spreadsheet-assisted thematic coding, the study identifies key narrative strategies such as micro-narrative formatting, stylistic modularity, and audience-personalised aesthetics. These strategies align with Lev Manovich’s concept of the database as a symbolic form and Henry Jenkins’s theory of convergence culture, in which audiences navigate content non-linearly across interconnected media systems. The findings demonstrate how Love, Death & Robots leverages Netflix’s platform affordances, including recommendation systems, interface architecture, and feedback loops, to promote a new logic of “algorithmic storytelling” targeting niche audiences and favouring episodic fragmentation over traditional seriality. While the series opens possibilities for genre hybridity and immersive world-building, it also reproduces ideological tensions, particularly in gender representation, illustrating that formal innovation does not inherently guarantee cultural progressiveness. This article contributes to scholarly debates on the aesthetics and politics of digital narratives by offering a platform-specific account of how storytelling is being reconfigured through algorithmic, modular, and immersive modalities. The research ultimately affirms the growing relevance of anthological storytelling as a viable and influential form in the algorithmic media landscape.